APLIKASI SVC (STATIC VAR COMPENSATOR) DALAM PERBAIKAN JATUH TEGANGAN PADA SISTEM KELISTRIKAN KOTA PALU - Masarrang, Maryantho (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2015)
By using PSAT application, which simulates SVC for voltage drop improvement across an electric power system, a good performance will be produced. The better an electric power system, the smaller voltage drop that occurs in the system. This study aims to improve the voltage drop across the feeder of Raflesia rayon Palu. By inspecting the result of discussion, it can be known that by simulating the installation of SVC, which is contained in PSAT application, a small voltage drop is obtained. Keywords: SVC, Voltage Drop, Feeder Raflesia